2014
DOI: 10.4236/abc.2014.42014
|View full text |Cite
|
Sign up to set email alerts
|

Brown Algae <i>Himantothallus grandifolius</i> (Desmarestiales, Phaeophyceae) Suppresses Proliferation and Promotes Apoptosis-Mediated Cell Death in Tumor Cells

Abstract: Marine algae have been used as food since ancient times and today are consumed as a regular part of the diet. In this study, we hypothesized that H. grandifolius phlorotannins-enriched extract exerts cytotoxic selective effects against tumor cell lines promoting cell death trough apoptosis mechanisms. The aim of the present study is to characterize chemically and investigate the selective cytotoxic effect of the H. grandifolius extract on epithelial tumour cell lines (A375, A549, Hep-2, HeLa) compared to non-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 42 publications
3
16
0
1
Order By: Relevance
“…The most evident changes in Caco-2 morphology, reflecting the hallmarks of cell apoptosis, were noticed at the highest concentration, i.e., 5% ( v / v ). Our observations are in good agreement with previous studies showing the cytotoxic effects of macroalgal extracts induced in breast cancer cell lines, and the series of morphological changes related to apoptosis, including cell shrinkage [35,36]. …”
Section: Discussionsupporting
confidence: 93%
“…The most evident changes in Caco-2 morphology, reflecting the hallmarks of cell apoptosis, were noticed at the highest concentration, i.e., 5% ( v / v ). Our observations are in good agreement with previous studies showing the cytotoxic effects of macroalgal extracts induced in breast cancer cell lines, and the series of morphological changes related to apoptosis, including cell shrinkage [35,36]. …”
Section: Discussionsupporting
confidence: 93%
“…Cytotoxicity of highest concentration (80 μg/mL) was showed~2 fold higher activity Control EAF (320 µg/mL) Quercetin (160 µg/mL) than that of lower concentration (20 μg/mL). Cytotoxicity of various extract obtained from a variety algae collectively demonstrated that the brown algae have a potential source of compounds presenting biological activities on tumor cells [34]. Cytotoxicity and antioxidant activity of EAF were found to be well correlated and concentration dependent.…”
Section: Discussionmentioning
confidence: 94%
“…Other report revealed that cell cycle arrest leads to increase in sub-G0/G1cell population after treatment with increasing doses of linalool terpenoid [36]. Phlorotanninsenriched extract of brown alga of H. grandifolius exhibited cytotoxicity against tumor cell line including Hep-2 and promoting cell death trough apoptosis mechanisms [34].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Statistical data revealed that TAA and cytotoxicity of S. marginatum were found to be well correlated along with concentration. Cytotoxicity of various extract obtained from a variety algae collectively demonstrated that the brown algae have a potential source of compounds presenting biological activities on tumor cells [19]. Recent report demonstrated that S. marginatum methanol extract powerfully inhibits cell proliferation of EAT and BeWo cells and less effect on non transformed HEK 293 cells.…”
Section: Discussionmentioning
confidence: 99%